2012
DOI: 10.1371/journal.pone.0038971
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Morphology of Hippocampal and Amygdalar Neurons in Adolescent Mice Is Resilient to Genetic Differences in Stress Reactivity

Abstract: Many studies have shown that chronic stress or corticosterone over-exposure in rodents leads to extensive dendritic remodeling, particularly of principal neurons in the CA3 hippocampal area and the basolateral amygdala. We here investigated to what extent genetic predisposition of mice to high versus low stress reactivity, achieved through selective breeding of CD-1 mice, is also associated with structural plasticity in Golgi-stained neurons. Earlier, it was shown that the highly stress reactive (HR) compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 67 publications
5
59
1
Order By: Relevance
“…For Golgi staining, mice aged 4 months were perfused with 0.9% NaCl and their brains treated with the Rapid GolgiStain Kit according to the manufacturer’s instructions (FD Neurotechnologies, Inc., PK401). Dendritic spines were quantified as described 69 . In short, images of pyramidal neurons of the CA1 region of the hippocampus were captured using a Axioplan bright-field microscope.…”
Section: Methodsmentioning
confidence: 99%
“…For Golgi staining, mice aged 4 months were perfused with 0.9% NaCl and their brains treated with the Rapid GolgiStain Kit according to the manufacturer’s instructions (FD Neurotechnologies, Inc., PK401). Dendritic spines were quantified as described 69 . In short, images of pyramidal neurons of the CA1 region of the hippocampus were captured using a Axioplan bright-field microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, it is possible that the differences in neuronal physiology between resilient and vulnerable rat existed before stress. However, a previous study that examined the morphology of BA neurons in high and low stress-responsive rodents did not find any difference (Pillai et al, 2012), whereas Adamec et al (2012) found significant dendritic hypertrophy in anxious control rats, but no further effect of stress. Furthermore, neuronal excitability of control rats was significantly less than stressed rats, before subdivision into resilient and vulnerable, indicating that stress had an overall impact on membrane properties.…”
Section: Discussionmentioning
confidence: 68%
“…Additionally, the dendritic complexity index (DCI) was calculated using the Neurolucida software as follows: DCI = (R branch tip orders + number branch tips) Â (total dendritic length/total number of primary dendrites). Branch tip order is determined by the number of bifurcations in a particular dendritic segment between a particular terminal tip and the cell body (Pillai et al, 2012). Dendritic arborization was analyzed using a Sholl analysis.…”
Section: Morphological Analysismentioning
confidence: 99%